2007
DOI: 10.1007/s11661-006-9033-1
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Observation of Texture Changes during Phase Transformations in Ultra-Low-Carbon Steel

Abstract: Texture changes during the a(bcc)-c(fcc) phase transformation in ultra-low-carbon (ULC) steel were investigated in situ by neutron diffraction, making use of a vacuum furnace. The initial texture is a typical bcc rolling texture. Upon heating above 500°C, it recrystallizes, and above 900°C, it transforms into an fcc texture with (111) fcc pole figures resembling (110) bcc and (110) fcc resembling (111) bcc. Upon cooling, the reverse transformation produces a texture that is close to the initial one, documentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The presence of strong texture through the phase transformation indicates that variant selection is active for the bcc Fe to fcc Fe phase transformation, as has been previously observed in ultra-low carbon steel. 53 The 110 maximum in the fcc phase remains the same with continued heating and deformation. This texture can also be generated by slip on {111}〈110〉 and is the typical compression texture in fcc metals.…”
Section: Iii-iv High Temperature Texturementioning
confidence: 95%
“…The presence of strong texture through the phase transformation indicates that variant selection is active for the bcc Fe to fcc Fe phase transformation, as has been previously observed in ultra-low carbon steel. 53 The 110 maximum in the fcc phase remains the same with continued heating and deformation. This texture can also be generated by slip on {111}〈110〉 and is the typical compression texture in fcc metals.…”
Section: Iii-iv High Temperature Texturementioning
confidence: 95%
“…For example, ferrite-to-austenite transformation occurring in an intercritical annealing range is known to indicate the memory effect. [3][4][5][6] There must be a rule that determines austenite orientation in relation to the initial ferrite texture. The variant selection of austenite during reverse transformation has been discussed in the literatures and several models have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of variant selection of transforming γ has been discussed in the literature. In studies on the texture memory effect during α−γ−α transformation [14][15][16][17][18][19][20][21][22] , it is commonly suggested that the γ texture after the reverse transformation is not randomly selected but is determined under the rule on the variant selection of transforming γ. Various models to explain the variant selection rules of transforming γ during reverse transformation have been proposed.…”
Section: Introductionmentioning
confidence: 99%